Response to olaparib in a PALB2 germline mutated prostate cancer and genetic events associated with resistance - Horak, Peter; Weischenfeldt, Joachim; Amsberg, Gunhild von; Beyer, Burkhard; Schütte, Andreas; Uhrig, Sebastian; Gieldon, Laura; Klink, Barbara; Feuerbach, Lars; Hübschmann, Daniel; Kreutzfeldt, Simon; Heining, Christoph; et al. (Cold Spring Harbor molecular case studies, 2019)
Prostate cancers harboring DNA repair gene alterations are particularly sensitive to PARP inhibitor treatment. We report a case of an advanced prostate cancer patient profiled within the NCT-MASTER (Molecularly Aided Stratification for Tumor Eradication Research) precision oncology program using next-generation sequencing. Comprehensive genomic and transcriptomic analysis identified a pathogenic germline PALB2 variant as well as a mutational signature associated with disturbed homologous recombination together with structural genomic rearrangements. A molecular tumor board identified a potential benefit of targeted therapy and recommended PARP inhibition and platinum-based chemotherapy. Single-agent treatment with the PARP inhibitor olaparib as well as subsequent combination with platinum-based chemotherapy resulted in disease stabilization and substantial improvement of clinical symptoms. Upon progression, we performed whole-exome and RNA sequencing of a liver metastasis, which demonstrated up-regulation of several genes characteristic for the neuroendocrine prostate cancer phenotype as well as a novel translocation resulting in an in-frame, loss-of-function fusion of RB1. We suggest that multidimensional genomic characterization of prostate cancer patients undergoing PARP inhibitor therapy will be necessary to capture and understand predictive biomarkers of PARP inhibitor sensitivity and resistance.